The Influence of Self-Actualization Needs, Awards, and Social Needs on The Work Achievements of Rantauprat State Court Officers - Christian Victor Samuel Wattimena; Siti Lam'ah Nasution; Yudi Prayoga (Quantitative Economics and Management Studies, 2022)
This study aims to analyzeThe Influence of Self-Actualization Needs, Appreciation and Social Needs on Work Performance of Rantauprapat District Court Employees. In this study, the population was 40 employees of the Rantauprapat District Court. Due to the number of employees of the Rantauprapat District Court, as many as 40 people (less than 100 people), then all employees are taken as objects of research. The analytical method used in this research is multiple linear regression. The results of the regression analysis obtained the t count value of 2.112 > t table 1.6883, this means that the self-actualization needs variable (X1) has a positive effect on the work performance variable (Y). Then the significant value is 0.042 <0.05, which means that the variable of self-actualization needs (X1) has a significant effect on the work performance variable (Y). Based on the results of the regression analysis, the t-count value was 2.131 > t table 1.6883. This means that the award variable (X2) has a positive effect on the work performance variable (Y). Then the significant value is 0.040 <0.05, which means the award variable (X2) has a significant effect on the work performance variable (Y). The results of the regression analysis obtained the t-count value of 3.774 > t table 1.6883, this means that the social needs variable (X3) has a positive effect on the work performance variable (Y). Then the significant value is 0.001 <0.05, which means that the social needs variable (X3) has a significant effect on the work performance variable (Y). The Fcount value is 37.995 > Ftable 2.86 with a significance value of 0.000 <0.05. From these results, it can be concluded that self-actualization needs (X1), appreciation (X2) and social needs (X3) simultaneously have a positive and significant effect on work performance (Y). The value of R Square from the analysis of the coefficient of determination is 0.760, meaning that work performance can be explained by the job rotation variable (X1), and experience (X2) by 76%.